AHP-Based Prioritisation of Cashless Payments in Indonesian SMEs: Evidence from Depok - Putri Kartika Sari; Jonathan Nahum Marpaung (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
Cashless payment platforms are increasingly central to the daily operations of Indonesian small and medium enterprises, yet recent Indonesian and regional evidence rarely quantifies the criteria trade-offs that managers confront when choosing among competing alternatives. This study addresses that gap by applying the Analytic Hierarchy Process to a healthy-food SME that accepts remote payments via GoPay, GrabPay, and ShopeePay and conducts in-store digital transactions through Electronic Data Capture and the Quick Response Code Indonesian Standard. Primary data were collected through structured pairwise-comparison interviews with owner-managers during March to April 2025 (n = 5), producing a criteria-level priority structure and ranked preferences that were verified for internal coherence. All final matrices met the AHP consistency requirement with Consistency Ratio values below 0.10, and a sensitivity analysis confirmed that the ordering of alternatives remained stable under plausible variations in criterion weights. The results show that cost and real-time transaction capability dominate the preference structure, while user-friendly features and promotion exert secondary influence. The findings offer actionable guidance for firms and providers through emphasis on effective fee design, reliable real-time settlement, interface simplification, and targeted promotions that strengthen adoption and customer experience.